Persistent CD19+ B cell lymphopenia in critically ill COVID-19 patients 50 days after symptom onset - An, Hui; Li, Ting; Zhang, Xinyue; Hu, Hao; Zhang, Chen; Wang, Yongyu; Jin, Shengwei; Li, Ming (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionLong COVID (LC) poses a persistent challenge in clinical practice due to limited understanding of its etiology. LC is hypothesized to stem from aberrant immune responses in COVID-19. Vaccinations, which boost immune cells to restore function, could help ease LC symptoms.MethodsTo exclude the impact of vaccination, we examined the immune cell profiles of recovering COVID-19 patients before vaccines were available. White blood cell differentials were monitored in ninety-twohealthy unvaccinated controls. Seventy-six unvaccinated COVID-19 patients were monitored upon admission and on the 50th day post-symptom onset (DPSO50). Peripheral lymphocyte subsets were analyzed using flow cytometry.ResultsMild cases showed no significant changes in lymphocyte counts or subsets from admission to DPSO50. By DPSO50, severe and critical cases showed almost complete recovery from lymphopenia, with critical cases having CD19+ B-cell counts approximately 45% lower than the mild group. Severe and critical cases exhibited reduced B-cell frequencies, with critical cases displaying around 48% higher natural killer (NK) cell counts. In mild cases, NK cell counts negatively correlated with B-cell counts (r=-0.528, p=0.02). Additionally, critical cases showed positive correlations between NK cell counts and CD4+ T-cell counts (r=0.83, p<0.01), and between NK cell counts and CD8+ T-cell counts (r=0.74, p<0.01). Severe cases demonstrated decreased counts of CD4+CD25+CD127lowFoxP3+ regulatory T-cells (Tregs), which positively correlated with B-cell counts (r=0.37, p<0.05).DiscussionOur findings indicate that aberrant immune cell profiles in COVID-19 patients change dynamically during recovery, depending on disease severity. This study suggests that convalescent patients from critical COVID-19 may experience long-lasting B-cell lymphopenia.